The Management System Auditor's Handbook - Kausek, Joe, 1957- (ASQ Quality Press, 2006)
"Meant for both new and experienced auditors, The Management System Auditor's Handbook provides a detailed and structured examination of the audit process. This book seeks to address the whys of auditing, as well as the whats and the how tos. Extensive focus is provided on auditing for effectiveness, in addition to conformance. Author Joe Kausek explains how to use your audit program to drive continual improvement and alignment throughout the organization through the identification of best practices and waste. A special chapter is devoted to the use of the internal audit program to verify deployment of the company's strategic plan or Balanced Scorecard. Unlike other audit books on the market, this handbook seeks to give the auditor sufficient understanding of the intent, techniques, and specific strategies for auditing, allowing for the development of an audit program that is uniquely fitted to the auditor's industry, processes, and company culture."--BOOK JACKET.Title Summary field provided by Blackwell North America, Inc. All Rights Reserved